Evaluation of drug interactions between fimasartan and rosuvastatin after single and multiple doses in healthy Caucasians - Lee J; Rhee SJ; Lee S; Yu KS (Dove Medical Press, 2018)
Jieon Lee, Su-jin Rhee, SeungHwan Lee, Kyung-Sang Yu Department of Clinical Pharmacology and Therapeutics, Seoul National University Hospital, Seoul National University College of Medicine, Seoul, Republic of Korea Objectives: As hypercholesterolemia is often accompanied by hypertension, statins are usually prescribed with angiotensin receptor blockers in clinical practice. This study was performed to evaluate the pharmacokinetics and safety of fimasartan and rosuvastatin when coadministered or administered alone as a single dose or as multiple doses to healthy Caucasians.Methods: Thirty-six subjects were enrolled into an open-labeled, randomized, 6-sequence, 3-period, 3-way crossover study, and randomly received fimasartan (120 mg), rosuvastatin (20 mg) or both. Blood samples for pharmacokinetics were collected up to 48 hours for fimasartan and 72 hours for rosuvastatin after the last dosing and plasma concentrations of study drugs were determined by liquid chromatography-tandem mass spectrometry. Maximum plasma concentration (Cmax), area under the concentration-time curve (AUC) from 0 to the last measurable time (AUClast), maximum plasma concentration at steady state (Cmax,ss) and AUC to the end of the dosing period at steady state (AUCτ,ss) were estimated using a non-compartmental method. Safety and tolerability were evaluated throughout the study.Results: Thirty subjects completed the study. After single dose administration, the geometric mean ratio (GMR) and 90% confidence intervals (CIs) of fimasartan with or without rosuvastatin were 0.95 (0.80–1.14) and 0.98 (0.91–1.07) for Cmax and AUClast, respectively. The corresponding values for rosuvastatin with or without fimasartan were 1.32 (1.16–1.50) and 0.97 (0.89–1.05), respectively. After administration of multiple doses, the GMRs (90% CIs) for Cmax,ss and AUCτ,ss of fimasartan with or without rosuvastatin were 0.94 (0.74–1.20) and 1.07 (0.90–1.16), respectively. The corresponding values for rosuvastatin with or without fimasartan were 1.16 (1.02–1.32) and 0.86 (0.79–0.94), respectively. A total of 74 adverse events (AEs) were reported and incidences of AEs did not increase significantly with co-administration.Conclusion: Co-administration of fimasartan and rosuvastatin did not result in clinically relevant changes in the systemic exposure of fimasartan or rosuvastatin after single and multiple administrations, and they were well tolerated. Keywords: fimasartan, rosuvastatin, drug interaction, clinical trial, angiotensin II receptor antagonist, healthy subjects